INPORTANCE OF TRACE ELEMENTS AND S-A ALBUMIN GRADIENT IN THE CIRRHOTIC AND NON-CIRRHOTIC ASCITES GROUPS - Ertan ULUSOY; Rıfat GÖZDAŞOĞLU; A. ALPER; K. DAĞALP; M. İsmet YILMAZER (Turkish Journal of Gastroenterology, 2020)
-